The Characteristics and Spatial Modelling of Informal Economies - Claude, Dounya Matsop; Ibrahim, Ngouhouo; Fantcho, Joseph Emmanuel; Ndesil, Tchuani Ngakam Ulrich (Asian Journal of Economic Modelling, 2020)
The goal of this study is to identify the characteristics of informal economies. Specifically, we identify the factors that describe informal economies and summarize them into indices measuring informality. We use data on 189 countries and the method used to analyze the data focuses only on the year 2012. We perform an exploratory analysis to identify the variables which structure informal economies and use the scores from a logistic regression to measure the degree of informality of each country. The results show that the degree of informality a country is related to its level of development. Thus, developing countries are generally those where the degree of informality is highest while developed countries are generally characterized by a low level of informality. This study thus enables us to classify countries into groups according to the variables that determine informality and draw a chart representing the countries according to their level of informality.